ANALISIS YURIDIS PERJANJIAN PENGIKATAN JUAL BELI (PPJB) ATAS SISTEM PRE PROJECT SELLING - selly, Selly; Ukas, Ukas (LPPM Universitas Putera Batam, 2021)
The sale and purchase binding agreement in the pre project selling system, is implemented with the aim of protecting the interests of the parties from default or breach of contract. The sale and purchase binding agreements in the pre project selling system are often identical to the standard agreement model whose contents have been determined unilaterally. In its development development to meet the flexibility and economic value of a condition in this pre project selling system, the sale and purchase binding agreement in addiction to being in the form of authentic deed, are also often made privately in the form of privately made deed. This study aims to find out how the legal standing of the sale and purchase binding agreement on the pre project selling system and the legal force of the sale and purchase binding agreement in the event that the parties default on the pre project selling system. The type of research used is normative research method, with the study process to find the rule of law to answer the issues.